Examining the journalistic genres hybridisation in content published by newspapers on Facebook Live (2020)
Journalistic appropriation of social networks and the popularisation of smartphones have influenced media content's production and the speed with which it circulates on networks. In this context, this article analyses journalistic genre hybridisation on Facebook Live streams from the newspapers Estadão (Brazil) and El Tiempo (Colombia). To conduct the case study, a content analysis was carried out on 40 videos broadcast by both newspapers on Facebook Live in July and August of 2017. The results show that this type of video favors journalistic genre hybridisation; hence, the use of hybrid genres in much of the content stands out and that this can influence the journalistic narrative in the coming years. © 2020, © 2020 Journal of International Communication.